2019
DOI: 10.3390/fractalfract3020017
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Fractal Dimension of the Fracture Network System Using Image Processing Technique

Abstract: Fractal dimension (FD) is a critical parameter in the characterization of a rock fracture network system. This parameter represents the distribution pattern of fractures in rock media. Moreover, it can be used for the modeling of fracture networks when the spatial distribution of fractures is described by the distribution of power law. The main objective of this research is to propose an automatic method to determine the rock mass FD in MATLAB using digital image processing techniques. This method not only acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…As fractal theory is now widely used [15][16][17][18][19][20][21][22][23], many researchers [24][25][26][27][28][29][30][31] have found that geomaterials exhibit fractal characteristics, and the rock joints, particle distribution, and pores at different scales have self-similarity, which is also consistent with the evolution of geomaterials under natural conditions. Generally, geomaterials can be regarded as an open non-linear self-organizing system.…”
Section: Introductionmentioning
confidence: 67%
“…As fractal theory is now widely used [15][16][17][18][19][20][21][22][23], many researchers [24][25][26][27][28][29][30][31] have found that geomaterials exhibit fractal characteristics, and the rock joints, particle distribution, and pores at different scales have self-similarity, which is also consistent with the evolution of geomaterials under natural conditions. Generally, geomaterials can be regarded as an open non-linear self-organizing system.…”
Section: Introductionmentioning
confidence: 67%
“…[26,29,30]. This method (i.e., calculating the fractal dimension by digital image processing) also was verified through manual and different methods by Basirat et al [31]. This process was applied in a macro-scale (outcrop photos) image and a micro-scale (CT-scan) image.…”
Section: Calculation Of Fractal Dimension (D) Using Digital Image Promentioning
confidence: 95%
“… Deposition, folding, shorelines, water flow, burial patterns below the surface [10].  Determining the relationship between lineaments and soil degradation processes [17]  Structural geology phenomenon [18].…”
Section: Fractalmentioning
confidence: 99%